Institutions, culture, and open source - Sebastian von Engelhardt; Andreas Freytag (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
The paper analyzes the impact of institutional and cultural factors on a remarkable economic activity: the production of so-called open source software (OSS). OSS is marked by free access to the software and its source code. Copyright-based OSS licenses permit users to use, change, improve and redistribute the software, which is designed and developed in a public, collaborative manner. OSS seems to be an example of a 'private provision of a public good'. While the supply-side microeconomics of OSS (individual characteristics of OSS developers, role of firms etc.) are well explored, it is not known which institutional and cultural factors explain different OSS activities across countries. For this reason, we perform a cross-country study analyzing how the number of OSS developers per inhabitants and the level of OSS activity of a country depend on institutional and cultural factors. Our findings are that a culture characterized by individualism/self-determination, abundance of social capital interpreted as interpersonal trust, an optimistic view of scientific progress, a low degree of regulation as well as good protection of intellectual property rights is favoring OSS activities. Our study thus contributes to the understanding of the role of cultural and institutional factors in general as well as in particular with respect to OSS. Additionally, it improves the understanding of the supply-side of OSS.
Keywords: B52; L17; L86; O34; Z13; Z19; 330; Open Source; Culture; Institutions; Social Capital; Trust; Regulation; Entrepreneurial Spirit; Individualism; Intellectual Property Rights; Open Source; Programmierung; Institutionelle Infrastruktur; Wirtschaftsethnologie; Social Capital; Unternehmer; Individualismus; Eigentumsrecht; Welt